2021
DOI: 10.1038/s41398-021-01221-0
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical connectivity is associated with autism symptoms in high-functioning adults with autism and typically developing adults

Abstract: Alterations in sensorimotor functions are common in individuals with autism spectrum disorder (ASD). Such aberrations suggest the involvement of the thalamus due to its key role in modulating sensorimotor signaling in the cortex. Although previous research has linked atypical thalamocortical connectivity with ASD, investigations of this association in high-functioning adults with autism spectrum disorder (HFASD) are lacking. Here, for the first time, we investigated the resting-state functional connectivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 75 publications
(111 reference statements)
3
18
0
Order By: Relevance
“…The PRC is the primary motor cortex (M1) and PC is the primary somatosensory cortex (S1). The implications of PRC and PC in ASD had been reported previously (32,33). Interestingly, we also found the functional connectivity including right S1 (S1R) and M1 (M1R) regions were specifically decreased in MECP2 transgenic monkeys, the non-human primate model for autism, comparing to wild-type monkeys (34)(35)(36).…”
Section: Expression Of Asd Risk Genes Enriched At Pc Prc and Bst Regions In The Developing Human Brainsupporting
confidence: 82%
“…The PRC is the primary motor cortex (M1) and PC is the primary somatosensory cortex (S1). The implications of PRC and PC in ASD had been reported previously (32,33). Interestingly, we also found the functional connectivity including right S1 (S1R) and M1 (M1R) regions were specifically decreased in MECP2 transgenic monkeys, the non-human primate model for autism, comparing to wild-type monkeys (34)(35)(36).…”
Section: Expression Of Asd Risk Genes Enriched At Pc Prc and Bst Regions In The Developing Human Brainsupporting
confidence: 82%
“…Prior research demonstrated the sensitivity of thalamus to language (Münte & Kutas, 2008), and various lines of evidence have observed the activation of thalamus in language-related tasks, such as phonological word retrieval processes (Perani et al, 2003) and verbal and semantic uency tasks (Rodrigo et al, 2008a). The abnormalities appeared in thalamus among ASD have also been discovered (Ayub, 2021;Tomasi & Volkow, 2019). Our results also revealed the increased FC between left thalamus and Broca area in ASD, indicating that atypical connectivity between Broca and thalamus might connect with the language dysfunction in ASD.…”
Section: Altered Fc Between Broca Area and The Whole Brain In The Con...supporting
confidence: 72%
“…The PRC is the primary motor cortex (M1) and PC is the primary somatosensory cortex (S1). The implications of PRC and PC in ASD had been reported previously 32,33 . Interestingly, we also found the functional connectivity including right S1 (S1R) and M1 (M1R) regions were speci cally decreased in MECP2 transgenic monkeys, the non-human primate model for autism, comparing to wild-type monkeys 34,35,36 .…”
Section: Expression Of Asd Risk Genes Enriched At Pc Prc and Bst Regions In The Developing Human Brainmentioning
confidence: 79%